Clinical and genetic determinants of worse sexual experience in male patients with radiographic axial spondyloarthritis: a multimodal study - Feng Huang; Jian Zhu; Yiwen Wang; Jianglin Zhang; Dai Gao; Xiaojian Ji; Lidong Hu; Xingkang Liu (RMD Open)
Objective The expression and experience of sexuality is a key part of an individual’s self-identity, yet it is often overlooked in clinical settings. This study aims to evaluate the impact of radiographic axial spondyloarthritis (r-axSpA) on sexual experience in male patients, identify contributing factors and explore the potential causal relationship between r-axSpA and erectile dysfunction (ED).Methods We assessed the sexual experience of 113 male patients with r-axSpA and 73 healthy people using the Sexual Experience Questionnaire in the cross-sectional study. Linear regression analysis was used to explore the contributions of clinical factors to worse sexual experience. A two-sample Mendelian randomisation (MR) design was conducted to examine the potential causal association of r-axSpA with the risk of ED.Results There was a significant difference in the total sexual experience score between patients with r-axSpA and healthy controls (41.81±8.71 vs 50.23±8.82, p<0.001). Patients with r-axSpA had a worse score in all dimensions of sexual experience, including erectile function, individual satisfaction and couple satisfaction, compared with healthy individuals. In the regression model adjusted for age, disease duration and body mass index, disease activity (Bath Ankylosing Spondylitis Disease Activity Index), physical function (Bath Ankylosing Spondylitis Functional Index), mobility (Bath Ankylosing Spondylitis Metrology Index, chest expansion and finger-floor distance), health index (Assessment of SpondyloArthritis international Society Health Index), sleep quality (Pittsburgh Sleep Quality Index) and psychological status (Hospital Anxiety and Depression Scale (HADS), HADS-Anxiety and HADS-Depression) were significant determinants of sexual experience. The two-sample MR analysis demonstrated no causal effect of r-axSpA on the risk of ED (OR: 0.973; 95% CI: 0.824 to 1.149; p=0.749) based on the inverse variance weighted method. Sensitivity analyses supported the result, with no evidence of directional pleiotropy.Conclusions Worse sexual experience was associated with increased disease activity, reduced mobility, lower health index, poor sleep quality and psychological status. Genetic-level evidence indicated no direct causal relationship between r-axSpA and ED. Therefore, actively assessing disease-related suffering and developing new management strategies are essential for improving sexual experience in patients with r-axSpA.